Effects of the Small-Sided Soccer Games on Blood Pressure in Untrained Hypertensive Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Clemente, Filipe Manuel (2021)
This systematic review with meta-analysis was conducted to assess the effects of small-sided games (SSGs)-based programs on the systolic and diastolic blood pressure of untrained hypertensive adults. The data sources utilized were Web of Science, Scopus, SPORTDiscus, and PubMed. The eligibility criteria were: (i) randomized controlled trials including a control group and an intervention group exclusively using soccer SSGs; (ii) intervention and control groups including an untrained hypertensive adult population; (iii) articles written in English; and (iv) only full-text and original articles. The database search initially identified 241 titles. From those, five articles were eligible for the systematic review and meta-analysis. The included randomized controlled studies involved five individual experimental groups and 88 participants, and 68 participants in the five control groups. The results showed a large and beneficial effect of SSG on systolic (ES = 1.69; 95% CI = 0.71 to 2.66; p = 0.001; I2 = 85.2%; Egger's test p = 0.101) and diastolic blood pressure (ES = 2.25; 95% CI = 1.44 to 3.06; p < 0.001; I2 = 74.8%; Egger's test p = 0.118) when compared to the control groups. The findings of the current systematic review and meta-analysis revealed consistent beneficial effects of recreational soccer SSGs on untrained men and women from the hypertensive population, although high levels of heterogeneity.